Virtual reality motor sensing exercise in patients with Parkinson’s disease: a scoping review - Lulu Zou; Xiaoqing Chen; Sisi Lei; Qingwen Hu (Frontiers in Rehabilitation Sciences, 2025)
BackgroundA scoping review of research on the application of virtual reality (VR) motor sensing exercises for patients with Parkinson's disease was conducted to identify the types of interventions, outcome indicators, and evaluation tools used and to assess the effectiveness of these exercises. The aim was also to provide a reference for future research in this area.MethodsThe aim of this scoping review was to examine the current status of research into the application of somatosensory virtual reality exercise for patients with Parkinson's disease. We conducted a systematic search of the PubMed, Cochrane Library, Web of Science, and Embase databases. The search time frame was from the date the library was established until 19 April 2025, with the included literature being screened and summarised.ResultsThe majority of the included studies reported improved rehabilitation outcomes for participants, suggesting that VR is beneficial for the rehabilitation of patients with Parkinson's disease. A total of 2,327 articles were retrieved, comprising 10 randomised clinical trials, 3 class-experimental studies, and 1 mixed study involving a total of 470 patients with Parkinson's disease.ConclusionThis scoping review provides a basis for the application of virtual reality somatosensory exercise in elderly patients with Parkinson's disease and lays the groundwork for future research and clinical practice. However, large-scale, high-quality randomised controlled trials are still needed to verify the feasibility of virtual reality somatosensory exercise for Parkinson's patients and to inform the development of targeted exercise programmes for this patient group.